Foreign Tourists’ Satisfaction Level of Three-Star Hotels Staff’s English Proficiency and Communication - ZAHEDPISHEH, NAHID (2017)
Tourism and hospitality industry has had a significant development during the last decades in Malaysia, and it is considered as one of the most intensive industries of the country. The hotel industry is a service-based industry, and one of its principal components is the human resource. Besides attraction, interest, service quality and perhaps facilities, visitors want to be able to communicate well with the hotel staff, and being satisfied during their stay in the hotel. Thus, the staff who come into faceto- face contact with foreign customers have to be competent in the English language, and it is always regarded as an asset for them. This study is aimed at identifying the level of satisfaction among the foreign customers on the English proficiency of the staff, working in 3-star hotels in the vicinity of Cameron Highlands. Data was collected through a questionnaire survey and semi-structured interview. The overall findings showed that grammatical accuracy and pronunciation were among problematic areas that need improvement, suggesting some levels of expectations by the tourist towards the accurate use of English among the hotel staff in their workplace. However, the respondents’ attitudes towards the hotel staff’s low proficiency in English were different based on their age, gender and education background, signifying the need for comprehensive enhancement of language training. The findings showed that the male respondents had better satisfaction level on the general proficiency compared to the female respondents. The findings also revealed that the younger respondents were more satisfied than the elderly respondents in relation to hotel staff’s fluency, grammar accuracy and general proficiency. Finally, respondents with higher education background were less satisfied in terms of vocabulary and grammar, compared to those of lower educational background. The findings of the study revealed that although the hotel staff have English knowledge learned from their background, they are still lacking in some aspects of the language.